Phytochemical Content Identification And Antioxidant Activity Test Of Ethanol Extract Parijata Fruit (Medinilla Speciosa Blume) In Bedugul Area, Bali, Indonesia - Mintari, Gusti Ayu Willem; Suada, I Ketut; Phabiola, Trisna Agung; Wijaya, Nyoman; Yuliadhi, Ketut Ayu; Bakar, Nor Kartini Abu (International Journal of Biosciences and Biotechnology; Vol 11 No 1 (2023): International Journal of Biosciences and BiotechnologyDO - 10.24843/IJBB.2023.v11.i01.p04, 2023)
Antioxidants are compound that function as free radical scavengers, these compounds can be found in parijata fruit (Medinilla speciosa Blume). The secondary metabolites of this fruit can be identified by the GC-MS method. The aims of study to identification of phytochemical content and test the antioxidant activity of the ethanol extract of Parijata fruit (Medinilla speciosa Blume) in the Bedugul area of Bali. This method is used because it is more sensitive and the results of the analysis are easy to understand. Using the GC-MS method, 11 organic compounds with a quality value of ? 90 were found in the ethanol extract of parijata fruit which have antioxidant, antimicrobial, and others. The 3 compounds with the highest Area Under Curve were 5-Hydroxymethylfurfural (AUC 31.05%); 1,2,3- Benzenetriol (AUC 22.32%); and 4H-pyran-4-one-2,3-dihydro-3,5-dihydroxy-6-methyl- (AUC 6.97%). These three compounds have antioxidant properties. Parijata fruit antioxidant activity test was tested with the DPPH method. The antioxidant activity of the ethanol extract of parijata fruit has an IC50 value of 11.26 mg/L, in the category of very strong antioxidant activity. So that with this category, parijata fruit can be given further treatment as food for health. In addition, compounds with antimicrobial properties can be used as biopesticide products in agriculture.